Einflussfaktoren auf die präklinische Anlage einer Zervikalstütze = Parameters influencing the preclinical application of cervical collars - Kreinest, Michael; Rauch, Geraldine (Der Unfallchirurg, 2017)
The application of cervical collars is a standard procedure in emergency care of trauma patients. It is often observed that the application of cervical collars is performed incorrectly, which may lead to reduced immobilization of the cervical spine. The objective of this study was to analyze the practical skills of professional emergency care providers concerning the application of cervical collars.